The influence of Instagram likes on consumer attitude and purchase intention of e-commerce users in Bosnia and Herzegovina - Erna Grcić-Rešidović; Ensar Mekić (Economic Review: Journal of Economics and Business, 2022)
The popularity of social media for business and marketing is on a definite rise. Although researchers are increasingly studying various aspects of SNS (social networking sites) marketing and e-commerce, there are still few studies into the impact of Instagram due to the relatively new nature of the application. Therefore, the main objective of this study is to provide an analysis of the statistical significance of Instagram likes on consumer attitude and purchase intention on a linked e-commerce site. The secondary objective is to compare demographic data based on age, gender, and educational categories of the respondents. The final aim is to bridge the gap in literature and provide practical implications which would be useful to professionals in brand and marketing management. Based on a systematic literature review, first order structural equation model was proposed and tested. The empirical data was derived from a survey of 166 subjects in Bosnia and Herzegovina. Upon the collection of data, factor analysis was conducted in SPSS to ensure the validity and reliability through items' loadings and Cronbach's Alpha values. Furthermore, the empirical hypothesis testing was conducted in SmartPLS 3 in order to investigate direct effects of variables in the model. The results indicated that there is a significant statistical impact of Instagram likes on consumer attitude and purchase intention. Currently, due to the relatively recent use of the app for business and marketing purposes, there is a very limited amount of research on consumers' involvement and attitude on Instagram and its impact on the likelihood of purchase. Therefore, one can consider the theoretical and practical implications of this study to be evident.
Keywords: M30; M31; Z13; 330; consumer attitude; involvement onseller's Instagram; attitude towards the seller's; Instagram account; purchase intention; e-commerce; s-commerce; SNS (social networking sites)